MODERNISASI DAN DEMOKRATISASI PENDIDIKAN ISLAM MENURUT FAZLUR RAHMAN - Suryadi, Ahmad; Damopolii, Muljono; ., Salahuddin (Universitas Islam Negeri Alauddin Makassar, 2021)
This study discusses the modernization and democratization of Islamic education according to Fazlur Rahman. This research was conducted with the aim of: 1) knowing the nature of the concept of modernization of Islamic education according to Fazlur Rahman. 2) knowing the nature of the concept of democratization of Islamic education according to Fazlur Rahman. 3) knowing the variety of modernization of Islamic education according to Fazlur Rahman and 4) knowing the variety of democratization of Islamic education according to Fazlur Rahman. Basically this research is a literature research or library research using a philosophical analysis approach and a historical approach. Data sources used are primary and secondary data sources. The results of this study indicate that the concept of modernization of Islamic education according to Fazlur Rahman, namely: education is the starting point for reform. Any renewal model in Islam would never have happened without the involvement of education in it. Fazlur Rahman emphasized the concept of democratization in freedom for humans to develop creative attitudes and knowledge that exist in humans in order to improve their lives. Furthermore according to Fazlur Rahman that education should be held by promoting the freedom of students, because without the existence of a creative attitude students are difficult to develop. The variety of modernization of Islamic education that was initiated by Fazlur Rahman includes five aspects, namely: The Purpose of Islamic Education, the Education System, Educators, Students, and Educational Facilities. The various types of democratization of Islamic education according to Fazlur Rahman are: respecting human potential and the development and implications of humans on Islamic education.